(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
This article is part of a broader study, the aim of which is to analyse the changes and novelties in the terminology and generally in the discourse of the economic field of today’s Albanian language, because not only did the change of political system in years ’90 have political characteristics, but it also had powerful impetus of socio-economic factors. The transition initiated in years ’90 would have as a political slogan: “We want Albania like the entire Europe!”, but also other new collocations such as “market economy”, “free market”, and the famous “white cheque” etc, or other appellations of international organisations such as “International Monetary Fund” (IMF), “World Trade Organisation” (WTO) etc. Through the analysis of terminology and generally economic discourse, we can point out great changes that have occurred in economic terminology due to the change of systems. First of all, the decommissioning or the semantic change of many words, terms, collocations of the socialist period and their substitution with new terms. Secondly, the natural but also rushing outpouring of the terminology of market economy, of processes related to the deep economic transition that occurred in Albania during years ‘90. The massive socio-economic changes have had wide reflection in administrative texts and other publications of economic character, articles in newspapers and magazines or publications of businesses’ advertisement etc.